Numerical study of Jeffrey nanomaterial flow with heat and mass transfer - Saira Shukat; Tasawar Hayat; Aneeta Razaq (Results in Engineering)
Present communication addresses the flow of Jeffrey nanomaterial due to the coaxial cylinders. Outer cylinder is taken fixed while inner cylinder moves. Brownian motion and thermophoresis characterize nanofluid characteristics. Formulation for the objected flow is first modeled and then relevant differential systems computed numerically employing bvp4c. The study captures novel aspects of flow, heat, and mass transfer. Graphical illustration leads to important results. Here, curvature parameter gives rise to temperature enhancement. Reduction in concentration is observed through Brownian motion and Schmidt number. Mass transfer rate through Brownian motion and skin friction coefficient by curvature have decreasing trends. These results provide an applicable solution to address engineering problems related to heat and mass transport in curved domains, including thermal management systems, rotating machines and nanofluid cooling technologies.